Kehidupan Digulis Dalam Novel Antara Hidup Dan Mati Atau Buron Dari Boven Digul Karya Wiranta Dan Pandu Anak Buangan Karya Abdoe’l Xarim M.S : Studi Historiografi - Adam Prima; Hendra Naldi (Jurusan Sejarah FIS UNP, 2022)
This research is a histiographic study that discusses the written life of two literary works entitled Between Life and Death Or Buron Dari Boven Digul by Wiranta and Pandu Anak Outcast by Abdul Karim M.S. The purpose of this research is first, to describe the picture of Digulis' life when he was exiled in the Boven Digul camp in the novel. Second, knowing the background of the author and the spirit of the times that became the background for the novel. The research method used in this research is the historical method. The stages of the historical method are heuristics, source criticism, interpretation, and histiography. The results of this study show that the novel Between life and death or Buron dari Digul describes how Digulis' life is about escapism and how social life is in the Boven Digul camp. In Pandu Anak Exiled, the main character describes that life in the Boven Digul exile camp aspires to erase class inequalities in society, but at the same time in Boven Digul Camp acknowledges inequality after dealing with reality. Keywords: Digulis, Histiography, Life This research is a histiographic study that discusses the written life of two literary works entitled Between Life and Death Or Buron Dari Boven Digul by Wiranta and Pandu Anak Outcast by Abdul Karim M.S. The purpose of this research is first, to describe the picture of Digulis' life when he was exiled in the Boven Digul camp in the novel. Second, knowing the background of the author and the spirit of the times that became the background for the novel. The research method used in this research is the historical method. The stages of the historical method are heuristics, source criticism, interpretation, and histiography. The results of this study show that the novel Between life and death or Buron dari Digul describes how Digulis' life is about escapism and how social life is in the Boven Digul camp. In Pandu Anak Exiled, the main character describes that life in the Boven Digul exile camp aspires to erase class inequalities in society, but at the same time in Boven Digul Camp acknowledges inequality after dealing with reality. Keywords: Digulis, Histiography, Life